Implementasi Aplikasi Import Menggunakan Bootstrap Studi Kasus PT Anugerah Ganda Perdana - Sansprayada, Arfan (LPPM STMIK ANTAR BANGSA, 2017)
AbstractÃ¢â‚¬â€ This writing implement on Bootstrap application with case studies PT Anugerah Ganda Perdanat a company engaged in the trucking services, which are companies that take care of the delivery of goods in the form of container/container either in bulk or small parties.Ã‚Â This application describes the details about the flow of information about the flow of information about the way of the commencement order will begin the process to finish. Trucking services are needed at every company where the freight forwarder is business and growing even though it appears simple but who would have thought to have tremendous market potential. BenefitÃ‚Â applications to be built is easier for the employee to perform the work in accordance with their respective division.Ã‚Â While benefiting fromÃ‚Â the management is able to see the companys profit and loss in detail and clearly. PT Anugerah Ganda Perdana is one of the trucking service company that has a customer or customers very much which serve the needs of customers will both freight export and import. Implementation using the Bootstrap is an application that is used in PT Anugerah Ganda Perdana for supporting either of the employee or the management company in detail and complete so as to provide convenience for all those involved in PT Anugerah Ganda PerdanaÃ‚Â IntisariÃ¢â‚¬â€ Penulisan ini mengimplementasikan aplikasi trucking menggunakan bootstrap dengan studi kasus PT Anugerah Ganda Perdana sebuah perusahaan yang bergerak dibidang jasa trucking, yang mengurusi pengiriman barang pada container atau petikemas. Aplikasi ini menggambarkan detail tentang alur informasi tata cara dimulainya order sampai selesai. Jasa trucking sangat dibutuhkan dimanaÃ‚Â jasa pengiriman barang merupakan bisnis yang semakin maju dan berkembang walau terlihat sederhana tapi mempunyai potensi pasar yang luar biasa. Manfaat aplikasi yang akan dibangun ini adalah mempermudah karyawan untuk melakukan pekerjaannya sesuai dengan divisi masing masing, sedangkan manfaat dari sisi management adalah dapat melihat profit dan loss perusahaan secara detail dan jelas. Implementasi menggunakan Bootstrap ini merupakan aplikasi yang digunakan pada PT Anugerah Ganda Perdana untuk mendukung sarana dari sisi karyawan ataupun management perusahaan secara detail dan lengkap. Ã‚Â Keywords : Logistic, System, Import.